2006
DOI: 10.1111/j.1526-4637.2006.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation in Intractable Interstitial Cystitis and Related Pelvic Pain Syndromes

Abstract: Many people suffering with interstitial cystitis (IC) and related pelvic pain syndromes do not benefit from the standard medical or surgical treatments. The pathophysiology of IC bears striking similarities to a wide variety of disorders driven by neurogenic inflammation, many of which may someday be controlled through neuromodulation. Because the bladder is accessible to repeated inspection, functional monitoring, biopsy, and collection of effluents, the study of neuromodulation in IC promises to yield import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…discomfort, burning and stinging sensation). Several studies of these co-morbidities have confirmed muscle over-activation, lack of voluntary control, inability to relax, shortening of muscles and trigger point referred pain, as well as hypersensitivity exacerbated by anxiety, sexual and physical activity (Bernstein et al 1992;Brookoff and Bennet 2006;Fitzgerald and Kotarinos 2003a, b;Oemler et al 2006;Weiss 2001). Ultimately, further research into these co-morbidities is required (Arnold et al 2006) but may show that vestibulodynia, clitorodynia, generalized vulvodynia, urethral syndrome and abacterial interstitial cystitis may share a common mediating mechanism and may be symptomatic of pelvic muscle dysfunction distinguished only by the locale of the pain.…”
Section: Discussionmentioning
confidence: 97%
“…discomfort, burning and stinging sensation). Several studies of these co-morbidities have confirmed muscle over-activation, lack of voluntary control, inability to relax, shortening of muscles and trigger point referred pain, as well as hypersensitivity exacerbated by anxiety, sexual and physical activity (Bernstein et al 1992;Brookoff and Bennet 2006;Fitzgerald and Kotarinos 2003a, b;Oemler et al 2006;Weiss 2001). Ultimately, further research into these co-morbidities is required (Arnold et al 2006) but may show that vestibulodynia, clitorodynia, generalized vulvodynia, urethral syndrome and abacterial interstitial cystitis may share a common mediating mechanism and may be symptomatic of pelvic muscle dysfunction distinguished only by the locale of the pain.…”
Section: Discussionmentioning
confidence: 97%
“…While the etiology is unknown, theories explaining the pathophysiology of PBS/IC include an altered urothelial barrier, neurogenic inflammation including mast cell infiltration and afferent sensitization (6,7,36,61). A recent study using cats with naturally occurring feline-type IC has demonstrated that capsaicin-sensitive DRG neurons exhibited an increase in cell size and had increased firing rates to depolarizing current pulses due to a reduction in low-threshold K ϩ currents elicited by membrane depolarization between Ϫ50 to Ϫ30 mV (46), as similarly found in our present and previous studies using cystitis rats.…”
Section: Discussionmentioning
confidence: 99%
“…SNM lessened intractable pelvic pain in these patients [64,65]. It is thought that by reestablishing pelvic floor muscle awareness, pelvic floor hypertonus can be decreased, which not only reduces symptoms of pelvic pain but also helps relieve symptoms such as daytime frequency and nocturia [63]. SNM is a promising new avenue for the treatment of refractory UCPPS [66].…”
Section: Sacral Neuromodulationmentioning
confidence: 99%
“…SNM is a potential therapy for UCPPS associated with pelvic floor dysfunction. Small studies have demonstrated this fact through the stimulation of afferent pathways of sacral roots and of motor fibers innervating pelvic floor muscles [63]. SNM lessened intractable pelvic pain in these patients [64,65].…”
Section: Sacral Neuromodulationmentioning
confidence: 99%